2019
DOI: 10.5530/pj.2019.11.229
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, HPTLC Fingerprint and Discriminant Analysis of Plantago major Leaves from Diverse Origins in Indonesia

Abstract: Introduction: Plantago major L. (Plantaginaceae) is a perennial herb having contribution to the folk medicine all around the world, including Indonesia with wide geographical distribution. Plant materials origin is one factor that significantly influences the quality of herbal medicines. Materials and Methods: In this paper, High-Performance Thin Layer Chromatography (HPTLC) method using pattern-oriented approach has been employed to evaluate the quality of Plantago major leaves collected from seven origins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…43,44 Chemometric methods could be applied as appropriate tools for every step of natural products biochemomteric research, including experiment design, data pre-processing, metabolite identification, variable selection, and modeling, 45 that offers an efficient route to meaningful interpretation of results in biochemometric. 35 Particularly, biochemometric has been reported for the detection of active agents with different bio-and chemical-activities, for example, antioxidant, [46][47][48][49][50][51][52][53][54] cytotoxic, 27,[55][56][57] and anti-inflammatory effects, [58][59][60][61] in addition to α-amylase and α-glucosidase and tyrosinase inhibitions, 57,[62][63][64][65][66] and vasorelaxant, 67 anthelmintic, 68 antidiabetic, 69 and phytotoxic 70 properties. List of published articles on biological activities using metabolomics as well as chemometric tools is presented in Tables 1-3.…”
Section: Chemometric and Biochemometric: Challenges And Stepsmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 Chemometric methods could be applied as appropriate tools for every step of natural products biochemomteric research, including experiment design, data pre-processing, metabolite identification, variable selection, and modeling, 45 that offers an efficient route to meaningful interpretation of results in biochemometric. 35 Particularly, biochemometric has been reported for the detection of active agents with different bio-and chemical-activities, for example, antioxidant, [46][47][48][49][50][51][52][53][54] cytotoxic, 27,[55][56][57] and anti-inflammatory effects, [58][59][60][61] in addition to α-amylase and α-glucosidase and tyrosinase inhibitions, 57,[62][63][64][65][66] and vasorelaxant, 67 anthelmintic, 68 antidiabetic, 69 and phytotoxic 70 properties. List of published articles on biological activities using metabolomics as well as chemometric tools is presented in Tables 1-3.…”
Section: Chemometric and Biochemometric: Challenges And Stepsmentioning
confidence: 99%
“…This method was thus proposed as an alternative to the marker-oriented method for controlling the quality of P. major. 52 The ability of certain fungal endophytes to alter the chemical diversity of their host plant was assessed in a study using 33 strains of endophytes fungi isolated from Euphorbia myrsinites L. and Alstonia scholaris (L.) R. Br. The metabolite profiles of the fungus samples were evaluated using HPTLC.…”
Section: Thin Layer Chromatography and Highperformance Thin Layer Chr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Free-radical scavenging method using DPPH was employed to screen the antioxidant activity of the derived extracts [20,21], with ascorbic acids as the reference compounds. The extract and the reference compound were each diluted until 5X concentrations.…”
Section: Measuring Antioxidant Activitiesmentioning
confidence: 99%
“…Previous studies have shown that the levels of active compounds in a plant can vary according to the cultivation area, such as its temperature, humidity, rainfall, altitude, and others (Kartini et al, 2019;Pisano et al, 2015;Yudthavorasit et al, 2014). These variations cause inconsistency in the quality and efficacy of herbal products.…”
Section: Introductionmentioning
confidence: 99%